IMPLEMENTASI NILAI-NILAI DEMOKRASI DALAM PENGAMBILAN KEPUTUSAN ORGANISASI UNTUK MENINGKATKAN ORGANISASI SISWA INTRA SEKOLAH (OSIS) DI SMK DARUS SYIFA KOTA CILEGON - Anton Aulawi; Srinawati Srinawati (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2019)
This research aims to find out how the implementation of democratic values ​​in the Intra-School Student Organization (OSIS) in Darus Syifa Vocational School, Cilegon City, especially in the organizational decision-making process carried out by the student council administrators. This study uses a qualitative approach that was developed through a descriptive analysis method. Data collection techniques used are observation, interviews, documentation studies and literature studies. Based on the results of research in the field it can be explained that the decision-making process that can be implemented in the Student Council includes certain majority agreements, procedures with minority group agreements and the approval of certain minority groups. These three elements are aspects contained in the decision making process where a decision is considered valid if approved by many people. This can be seen in the deliberations carried out by the Student Council in the Darus Syifa Vocational School in Cilegon, Banten where the decisions made were based on the majority of votes. Walaw even in reality there are still many that need to be increased again such as the level of participation of the Student Council administrators in expressing their opinions so that the deliberation process is more active and not passive to get the best solution from the problem.